1995
DOI: 10.1099/0022-1317-76-2-401
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide and deduced amino acid sequence of the structural protein genes of Japanese encephalitis viruses from different geographical locations

Abstract: Strain variation among Japanese encephalitis (JE) virusisolates has been previously demonstrated by many workers using different methods. We report the nucleotide sequence of the 5' non-coding region and the nucleotide and deduced amino acid sequences of structural protein genes for eight wild-type JE virus strain isolated from different Asian countries (Vietnam, Nepal, Indonesia, Thailand, India, Japan and China). We compare these with five other published wild-type JE virus strains isolated from Japan and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…The second strain of virus (JE-P3) was isolated from mosquitoes in China in 1949 and had been passaged extensively in suckling mice and cultured cells. 22 Molecular sequencing of the pre-membrane region of both viruses confirmed that the viruses represented genotypes I (JE-VN) and III (JE-P3) respectively.…”
Section: Methodsmentioning
confidence: 96%
“…The second strain of virus (JE-P3) was isolated from mosquitoes in China in 1949 and had been passaged extensively in suckling mice and cultured cells. 22 Molecular sequencing of the pre-membrane region of both viruses confirmed that the viruses represented genotypes I (JE-VN) and III (JE-P3) respectively.…”
Section: Methodsmentioning
confidence: 96%
“…The functional significance of this high level of nucleotide variation within this 240 nt prM region has therefore yet to be established. 17 Indeed, earlier reports have shown that the use of short stretches of nucleotides or amino acids in phylogenetic analysis 35,36 results in incorrect tree topologies, suggesting that the 240 nt prM region is not the ideal candidate for studying the molecular evolution of JEV.…”
Section: Resultsmentioning
confidence: 99%
“…9 Immunotyping and oligotyping data suggest that strain variation among JE viruses is not related to geographic location. 16,[37][38][39] Comparison of nucleotide and amino acid sequence of envelope genes of thirteen JEV strains 17 showed no clustering based on geographical location. However, Chen and coworkers 9 used forty-six prM sequences to show that JEV isolates from the same geographic region and time period are similar.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…@7 Compar ative study of the nucleotide and deduced amino acid se quences of the core (C), pre-membranc (prc-M), membrane (M), and envelope (E) coding regions between five JEV strains, Nakayama-RFVL, Beijing-l, Kamiyama, Muar, and 691004, suggested that the Muar strain was the most struc turally different from the other four strains, in agreement with the results using a hcmagglutination inhibition test with JEV-spccics-specific monoclonal antibodies.4 Primer-exten sion sequencing of the gcnomic RNA template of JEV has provided new information on the geographic distribution, or igin, and evolution of this virus.5 6 Two hundred forty nu cleotides from the pre-M gene region of JEV isolates were analyzed, and the results showed the existence of four dis tinct JEV genotypes in Asia and suggested that genetic van ations occurred among strains from different time periods in the same region. In addition, it has been recently reported that the nucleotide sequence of the pre-M protein region was the most variable among the structural protein genes C, pre-M, M, and E. 7 The purpose of this study was to analyze 12 JEV strains isolated in three regions of Malaysia from 1993 to 1994, and to explore their genetic relationships.…”
mentioning
confidence: 99%